2018
DOI: 10.1186/s13104-018-3822-7
|View full text |Cite
|
Sign up to set email alerts
|

Poliovirus excretion following vaccination with live poliovirus vaccine in patients with primary immunodeficiency disorders: clinicians’ perspectives in the endgame plan for polio eradication

Abstract: ObjectivePrimary immunodeficiency (PID) patients are prone to developing viral infections and should not be vaccinated with live vaccines. In such patients, prolonged excretion and viral divergence may occur and they may subsequently act as reservoirs in the community introducing mutated virus and jeopardizing polio eradication. One hundred and thirty PID cases were included for poliovirus detection in stool with assessment of divergence of detected polioviruses from oral polio vaccine (OPV) virus. Clinical pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 18 publications
0
4
1
Order By: Relevance
“…The rate of asymptomatic iVDPV infection in our national study (2.6% overall; 3.1% in adaptive immunity defects) was several folds higher than this rate in a previous multinational report (0.8%) ( 15 ), despite a comparable proportion of SCID in both studies. Other studies also reported detection rates several times lower than what we observed in nonparalyzed PID patients ( 23 25 ). These differences can be caused by different proportions of PID types among these studies or the predominance of certain genetic defects or other predisposing factors in different countries.…”
Section: Discussioncontrasting
confidence: 82%
“…The rate of asymptomatic iVDPV infection in our national study (2.6% overall; 3.1% in adaptive immunity defects) was several folds higher than this rate in a previous multinational report (0.8%) ( 15 ), despite a comparable proportion of SCID in both studies. Other studies also reported detection rates several times lower than what we observed in nonparalyzed PID patients ( 23 25 ). These differences can be caused by different proportions of PID types among these studies or the predominance of certain genetic defects or other predisposing factors in different countries.…”
Section: Discussioncontrasting
confidence: 82%
“…In a study conducted on 130 patients with suspected or confirmed PID disorders, 6 patients were excreting VDPV, in which 5 of them had SCID and had X-linked agammaglobulinemia. Three patients developed acute flaccid paralysis (48). This underscores the importance of implementing the newborn screening programs, despite limited resources, for early diagnosis of PIDs and prevention of vaccination complications.…”
Section: Status In Egyptmentioning
confidence: 77%
“…Other iVDPV cases have been detected during the detection of enterovirus infection in children with suspected or confirmed PID through stool cultures. Among the iVDPV cases reported, 56% of iVDPVs were type 2, 23% were type 3, 17% were type 1, and 4% were heterotypic mixtures [ 6 ]. However, after the global removal of OPV2 from routine immunization in 2016, the incidence of iVDPV2 detection declined markedly.…”
Section: Discussionmentioning
confidence: 99%
“…Primary immunodeficiency diseases are a heterogeneous group of over 450 genetic disorders of the immune system [ 5 ], among whom patients with combined immunodeficiency diseases and antibody deficiencies are particularly at a high risk of prolonged excretion of VDPV after vaccination with OPV or close contact with a vaccinated individual [ 6 , 7 , 8 , 9 ]. PID patients may continue to excrete VDPV for a long duration asymptomatically and, thereby, act as a source of poliovirus reintroduction in the community.…”
Section: Introductionmentioning
confidence: 99%